The main ternds and features of professional training of teachers of German in Ukraine (Pedagogy of Higher and Secondary Education, 2016)
Dzewizka L. S. The main ternds and features of professional training of teachers of German in Ukraine.The article highlights the main trends and features of professional training of teachers of German in Ukraine. Leading trends, models and methods of professional training of teachers of German at higher educational institutions of Ukraine in the system of education and modern philosophy of the European higher pedagogical education were determined.The author draws attention to the nature, forms of training of future specialists in German in Ukrainian pedagogical universities, namely the establishment of national standards for teachers of German, reforming continuing education of teachers, improving the professionalism and social status of teachers, improving the competitiveness of educational institutions that train teachers of German language.Professional competence of teachers of German (professional and business competence, professional-didactic competence, competence of relationships, competence of training, organizational competence, selfcompetence) has aquired a separate consideration, as it is a significant international experience that was used during the standardization and modernization of higher pedagogical education in the context of the Bologna process.Basic principles of training of teachers of German are considered in the context of comparing with the educational system of teacher training in Austria.Higher School of Education today is in search of the optimal training of future teachers and effective technologies for their education readiness for pedagogical activities. Historically the unique system of training teachers has been developed in every European country, which facets should be investigated to determine the expediency of implementing promising ideas into practice taking into the consideration the features of the country.The perspective ways of creative use of training of the future teachers of German language schools in Austria and in Ukraine have been determined in this article.
Keywords: foreign language; cross-cultural competence; lifelong learning; innovative features of teaching and educational process at school; university cooperation